Seismic behavior of steel-reinforced high-strength concrete composite beams with bonded tendons - He, Jinjin; Jiang, Liangqin; Ji, Jing; Zhang, Zhanbin; Chu, Xuan; Hong, Yigang; Zhang, Huiling (Frontiers in Materials, 2023)
To study the seismic behavior of steel-reinforced high-strength concrete composite beams with bonded tendons (PSRHSCBs) under low cyclic loading, 13 PSRHSCBs were designed with the main parameters of the span-to-height ratio of beams (L/H), the cubic strength of concrete (fcu), the eccentricity of H-shaped steel (eH), the volume stirrup ratio (pv), the longitudinal reinforcement ratio (p), and the tension control stress of tendons(σcon). Using the simplified bilinear constitutive model of steel and the nonlinear constitutive model of high-strength concrete, and introducing plastic damage of concrete, fine finite element models were established with ABAQUS software. 11 similar test specimens were conducted by above modeling method, by comparing existing test curves and numerical simulation curves, both of them match well, which verified the validity of the modeling method. Subsequently, parameter analysis for 13 PSRHSCB specimens was performed, and the influence regularity of different parameters on the seismic behavior of this kind of composite beams was obtained. The results show that hysteretic curves of this kind of composite beams are full, and the failure mode is manifested as bending failure. The ultimate load, the energy dissipation capacity and the ductility coefficient of specimens can be improved significantly by increasing pv, on the contrary, the energy dissipation capacity and the ductility coefficient decrease gradually by increasing fcu. The stiffness degradation of specimens significantly slows down with the increasing of L/H and σcon, and the decreasing of eH. Finally, the trilinear skeleton curve model and the restoring force model are established by statistical regression, and the corresponding seismic design suggestions are given, and these can provide theoretical support for the seismic design of such composite beams in actual engineering.